Migration in Italy is Backing the Old Age Welfare - Daniela Del Boca; Alessandra Venturini (Institute for the Study of Labor (IZA), 2014)
Our research analyzes the effect of changes in migration policies and the accession to the European Union of former countries of emigration, considering the crucial role played by migrants in an aging society. We focus on the demand of family-care workers by using the last five years of the Italian Labour Force Survey dataset. Our results show that especially during the last years of recession, foreign labor (mostly female) has become fundamental in the family sector, favoring the participation of Italian skilled women in the labor market.
Keywords: J6; J15; F66; 330; migration; aging; women's work